2010
DOI: 10.1002/jez.620
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute carbon dioxide on behavior and physiology in Procambarus clarkii

Abstract: Vertebrates and invertebrates show a similar response of rapid anesthesia with high levels of carbon dioxide. In this study, we use crayfish to examine both behavioral and physiological responses to increasing [CO(2)] to explain the rapid unresponsiveness and cessation of an autonomic response. Hypoxic and low pH environments that are induced by CO(2) exposure were also examined, although neither produced the identified CO(2) effects. In insects, low concentrations play a vital role in providing information fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…It is well known that CO 2 has an effect on electrical communication by uncoupling gap junctions (Arellano et al, 1990). It was recently shown that the nerve cord and communication within the sensory-CNS-motor-muscle circuit, as described in this report, is also sensitive to CO 2 exposure, indicating the presence of gap junctions (Bierbower, 2010;Bierbower and Cooper, 2010) The spontaneous activity of the 3 rd motor root has been a topic since the 1960's when Eckert (1961) examined if the tonic firing static muscle receptor organ (MRO) within the same or neighboring segment could account for the spontaneous motor drive. In these earlier studies it became apparent that the activity was driven within the ventral nerve cord (VNC) possibly from higher centers (Eckert, 1961 .…”
Section: Measuring Synaptic Responsesmentioning
confidence: 53%
See 1 more Smart Citation
“…It is well known that CO 2 has an effect on electrical communication by uncoupling gap junctions (Arellano et al, 1990). It was recently shown that the nerve cord and communication within the sensory-CNS-motor-muscle circuit, as described in this report, is also sensitive to CO 2 exposure, indicating the presence of gap junctions (Bierbower, 2010;Bierbower and Cooper, 2010) The spontaneous activity of the 3 rd motor root has been a topic since the 1960's when Eckert (1961) examined if the tonic firing static muscle receptor organ (MRO) within the same or neighboring segment could account for the spontaneous motor drive. In these earlier studies it became apparent that the activity was driven within the ventral nerve cord (VNC) possibly from higher centers (Eckert, 1961 .…”
Section: Measuring Synaptic Responsesmentioning
confidence: 53%
“…One can try heptanol or CO 2 bubbled saline since it will uncouple the crayfish septate (or gap) junctions within the circuit as Dr. Sonya M. Bierbower (University of Kentucky) has shown in her dissertation research. This action may account for altered whole animal behavior when exposed to high CO 2 in the environment (Bierbower and Cooper, 2010). When you stimulate the cuticle with a brush and drive sensory input and record a response in the motor neurons, note if there is a difference in the activity before and during heptanol or CO 2 exposure.…”
Section: ) Dissectionmentioning
confidence: 99%
“…Some of the mechanisms, at a neuronal circuit level, which could account for the decreased behavioral responses induced by high levels of environmental CO 2 (as presented in Bierbower and Cooper, 2010) are presented in this study. Since rising CO 2 also resulted in a reduction of pH o , this variable needed to be addressed throughout these studies.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the heart and ventilation rates also showed complete cessation with high acute exposure within the same time period that the unresponsiveness to mechanosensory stimulation occurred. We suggested the CO 2 rises within the animal and has a direct action on the neuromuscular junction as well as on CNS, which accounts for the behavioral and physiological changes (Bierbower and Cooper, 2010). The crayfish nervous system presents several features which feasibly enable the study of a multitude of questions.…”
mentioning
confidence: 99%
“…Our experimental design is well suited for theoretical modeling, and we anticipate that more accurate mathematical models of agonistic interactions can be placed into the context of trade-offs with relevant abiotic constraints for subsequent empirical testing. To help understand the driving forces that influence the competitive context of crayfish in the wild, future research may consider whether other naturally varying environmental parameters, such as dissolved oxygen, carbon dioxide (see Bierbower and Cooper, 2010) or water flow, are also resources over which crayfish will compete.…”
Section: Discussionmentioning
confidence: 99%